Diagnostic Accuracy of the Cepheid 3-gene Host Response Fingerstick Blood Test in a Prospective, Multi-site Study: Interim Results. (22nd September 2021) - Sutherland, Jayne S; van der Spuy, Gian; Gindeh, Awa; Thuong, Nguyen Thuy Thuong; Namuganga, AnnRitah; Owolabi, Olumuyiwa; Mayanja-Kizza, Harriet; Nsereko, Mary; Thwaites, Guy; Winter, Jill; Dockrell, Hazel M; Scriba, Thomas J; et al.
Abstract: Background: The development of a fast and accurate, non-sputum-based point-of-care triage test for tuberculosis (TB) would have a major impact on combating the TB burden worldwide. A new fingerstick blood test has been developed by Cepheid (the Xpert MTB Host Response [MTB-HR] prototype), which generates a "TB score" based on messenger RNA (mRNA) expression of 3 genes. Here we describe the first prospective findings of the MTB-HR prototype. Methods: Fingerstick blood from adults presenting with symptoms compatible with TB in South Africa, The Gambia, Uganda, and Vietnam was analyzed using the Cepheid GeneXpert MTB-HR prototype. Accuracy of the Xpert MTB-HR cartridge was determined in relation to GeneXpert Ultra results and a composite microbiological score (GeneXpert Ultra and liquid culture) with patients classified as having TB or other respiratory diseases (ORD). Results: When data from all sites (n = 75 TB, 120 ORD) were analyzed, the TB score discriminated between TB and ORD with an area under the curve (AUC) of 0.94 (95% confidence interval [CI], .91–.97), sensitivity of 87% (95% CI, 77–93%) and specificity of 94% (88–97%). When sensitivity was set at 90% for a triage test, specificity was 86% (95% CI, 75–97%). These results were not influenced by human immunodeficiency virus (HIV) status or geographical location. When evaluated against a composite microbiological score (n = 80 TB, 111 ORD), the TB score was able to discriminate between TB and ORD with an AUC of 0.88 (95% CI, .83–.94), 80% sensitivity (95% CI, 76–85%) and 94% specificity (95% CI, 91–96%). Conclusions: Our interim data indicate the Cepheid MTB-HR cartridge reaches the minimal target product profile for a point of care triage test for TB using fingerstick blood, regardless of geographic area or HIV infection status. Abstract : This study is the first prospective evaluation of the Cepheid MTB-HR test using fingerstick blood in a multi-site cohort. Interim results indicate the test reaches the WHO TPP for a TB Triage test regardless of geographical location and HIV status.